Життєві університети першого секретаря ЦК КПУ Петра Шелеста - Бажан, О. (Краєзнавство, 2020)
У статті систематизовано і уточнено основні етапи першого періоду життя та професійного
шляху майбутнього партійного керівника Української РСР Петра Юхимовича Шелеста, з’ясовано
чинники й обставини, що визначили особливості політичної кар’єри політика. The article examines the path of becoming the highest echelon representative of the party-state nomenclature
of the USSR and the Ukrainian SSR on the example of the political biography of the First Secretary of the
Central Committee of the Communist Party of Ukraine, member of the Politburo of the Central Committee of
the Communist Party of the Soviet Union Petro Shelest. Themain stages of the first period of life and professional
path of the future party leader of the Ukrainian SSR are systematized and clarifiedon the basis of memoirs,
interviews, archival documents. In addition, there are clarifiedthe factors and circumstances that determined
the features of the politician’s political career.